ANALISIS FLYPAPER EFFECT PADA PEMERINTAH KABUPATEN/KOTA BERDASAR KELOMPOK INDEKS PEMBERDAYAAN GENDER - Maulana, Al Abidha Dinda; Maryunani (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Over the past two decades, fiscal decentralization in Indonesia has been predominantly focused on the expenditure side. East Java has a higher average regional expenditure realization compared to DKI Jakarta and DI Yogyakarta, but not with the average economic growth rate, thus raising the possibility of expenditure deviation in the form of the flypaper effect phenomenon. On the other hand, gender equality has become one of the urgencies in development and correlates with economic growth. Therefore, a quantitative study was conducted using panel data regression techniques (regional expenditure, PAD, and DAU) from all regencies/cities in East Java during 2018 to 2022, differentiated based on the Gender Development Index (GDI) value. This research aims to identify the existence of the flypaper effect, which can provide a general overview of the preferences in the use of regional expenditure funding sources. The results of this study found no flypaper effect in either high-GDI or low-GDI regencies/cities because the influence of PAD is more significant compared to DAU.